Enhancing English Language Proficiency in HRM: A Strategic Imperative for Logistics Efficiency - Rahmawati, Yusi; Mege, Stacia Reviany (Asian Journal of Logistics Management, 2023)
Good human resource management is critical to organizational success in the frantic logistics environment. The importance of English language skills in this setting cannot be overstated. This study piece dives into the interconnected connection between human resource management and English language abilities in the logistics sector. The internationalization of trade and the spread of supply chains across borders has prompted the development of a common language for communication. English, as the international corporate lingua franca, is critical in overcoming linguistic gaps across varied logistics teams and stakeholders. This article discusses the significant impact that English proficiency has on numerous facets of logistics operations. This study looks into the critical importance of English language competency in human resource management in the logistics industry, focusing on cross-cultural communication, talent acquisition, and retention. A comprehensive analysis of the literature, case studies, and surveys within the logistics industry was conducted to assess the significance of English language skills. Our research demonstrates a significant link between English language competency and effective cross-cultural communication, which is essential for timely information exchange in logistics operations. The strategic importance of English language ability for logistics organizations is highlighted by this research. In order to enable the staff to communicate effectively and promote operational excellence, it highlights the need for ongoing investment in language training programs. The findings of this study highlight the fact that comprehending English is a strategic need in the field of global logistics, not just a desired talent.